Prevalência de alterações auditivas em recém-nascidos em hospital escola - GUIMARÃES, Valeriana de Castro (2011)
Thesis presented in the form of scientific article and with the demonstration of three articles. In the first manuscript, published to the journal Ciência & Saúde Coletiva, Vol. 15, number 2, 2010, pages 559 to 562, entitled Hearing evaluation in newborn and its ethical implications, a bibliographic review of articles published in national magazines in Brazil were realized and had as purpose to examine the literature production that investigates the use of otoacoustic emissions test performed in newborns in hospitals, emphasizing the adoption of that article to the of Research Ethics Committee.The second accept to the journal Distúrbios da Comunicação PUC-SP has as title Maternal feelings and expectations concerning the result of the Neonatal hearing screening. It is a descriptive study on qualitative approach, and it had as objective investigate the maternal feelings and expectations expressed by the newborn mothers concerning the result of the Neonatal hearing screening. The data had been collected by means of individual interview with the newborn mothers and the following parameters had been analyzed: suspicion on the hearing of the son, knowledge about the deafness and expectations about the result. The third article, object of this thesis, submitted to the journal Ciência & Saúde Coletiva entitled as Prevalence of auditory changes in newborns in a teaching hospital, had as purpose estimate the prevalence of auditory changes in newborns in a teaching hospital. Prospective cross-sectional study that evaluated 226 newborns, born in a public hospital, and they had hearing screening after discharge from May, 2008 to May, 2009. The prevalence of auditory changes in this population was 0,9%. The current study offers relevant epidemiological data, providing preliminary results for future deployment and development of a neonatal hearing screening program. Considering the importance that demands the moment, the family deserves special attention of the health professionals involved in the process, before a deafness diagnosis.